Analysis of sense of places effect on tourist’s length of stay in the Khota Baru cultural heritage zone - Nik Mohamad Aizat Nik Mohd Adib; Syakir Amir Ab Rahman (EMARA: Indonesian Journal of Architecture, 2020)
Heritage and cultural tourism are part of the tourism industry that must be maintained sustainability. Therefore heritage tourism destinations must be able to carry a “sense of place” as its focus. A sense of place is essential in attracting tourists to visit heritage sites for a long time. This article aims to assess the relationship between the Sense of Place between tourists, domestic and international, and the length of stay in the Kota Bharu Cultural Heritage Zone. A total of 445 tourists participated as respondents by filling out a questionnaire survey. At the same time, data analysis was carried out using One way ANOVA. The results showed that the Sense of Place in the Kota Bharu Cultural Heritage Area affects tourists' length of stay with eight correlated scales. Those eight scales are authenticity, historical value, distinction, harmony, maintainability, and cleanliness. This study also finds several important implications for local governments and tourism practitioners in maintaining a tourism destination's economic and social attributes. This study is expected to serve as the basis for future studies related to the design of urban areas and other heritage tourism sites